Correlation between novel compound heterozygous ADAMTSL4 variants and primary phenotypes of ectopia lentis et pupillae. (November 2022) - Zhao, Junhong; Zhou, You; Zhang, Jing; Zhang, Kejin; Shang, Lijun; Li, Junlin
Abstract: Purpose: To investigate molecular pathogenesis of congenital ectopia lentis accompanied by various ophthalmic manifestations in a pedigree. Methods: Three female siblings, their spouse and offspring underwent ophthalmic and general medical examinations. Genetic variants were screened with the whole exome sequencing and analyzed in either a dominant or recessive inheritance manner. Gene mutations were ascertained with the Sanger sequencing after the polymerase chain reaction. Results: All three female siblings were diagnosed as the Ectopia lentis et pupillae (ELeP) through combination of clinical examination and genetic analysis. No characteristic pathological changes of skeletal, metabolic and cardiac abnormalities were observed. Thirteen genetic variants were selected out through analyzing in the dominant or recessive inheritance manner, but they were not associated with EL. Among them, ALOX15B variant may explain the skin disease in this pedigree. After inspection the known genes related to EL, novel compound heterozygous mutations (p.Ser264LeufsX37/p.Gly757ValfsX62) in ADAMTSL4 were discreetly identified in this ELeP pedigree. Conclusions: Novel compound heterozygous ADAMTSL4 variants are responsible for ELeP in the current pedigree. Correlation between ADAMTSL4 variants and ELeP was firstly established based on our 12 years follow-up studies and previous reports of ELeP and of ADAMTSL4 –related eye disorders. The primary phenotypes caused by ADAMTSL4 variants include EL, EP, poor pupillary dilation, and axial elongation. Highly varying phenotypes including glaucoma, high myopia retinapathy, and poor vision and so on may be the secondary impairments. All these secondary impairments may be improved if proper clinical interventions are implemented in time. Highlights: Novel compound heterozygous ADAMTSL4 variants identified in an ELeP pedigree. Combining our studies and previous reports, primary phenotypes of ELeP are concluded as EL, EP, poor pupillary dilation, and axial elongation. Secondary impairments including glaucoma, high myopia retinapathy, poor vision and so on, may be improved with proper clinical interventions.